Reconstruction of energy conditions from observations and implications for extended theories of gravity - Penna-Lima, M.; Vitenti, S. D.P.; Alves, M. E.S. [UNESP]; de Araujo, J. C.N.; Carvalho, F. C. (Springer Nature, 2019)
The attempt to describe the recent accelerated expansion of the Universe includes different propositions for dark energy models and modified gravity theories. Establish their features in order to discriminate and even rule out part of these models using observational data is a fundamental issue of cosmology. In the present work we consider a class of extended theories of gravity (ETG) that are minimally coupled to the ordinary matter fields. In this context, and assuming a homogeneous and isotropic spacetime, we derive the energy conditions for this ETG class. We then put constraints on these conditions using a model-independent approach to reconstruct the deceleration function along with the Joint Light-curve Analysis (JLA) supernova sample, 11 baryon acoustic oscillation and 22 cosmic-chronometer measurements. We also consider an additional condition imposing the strong energy condition only on the ordinary matter. This is to guarantee the presence of only attractive matter in the energy–momentum tensor, at least in the redshift range of the observations, i.e., the recent accelerated expansion of the Universe is due solely to the modifications in the gravity theory. The main result of this work is a general reconstruction of the energy conditions valid for every considered ETG.